3D image‐based navigators for coronary MR angiography. Issue 5 (13th May 2016) - Addy, Nii Okai; Ingle, R. Reeve; Luo, Jieying; Baron, Corey A.; Yang, Phillip C.; Hu, Bob S.; Nishimura, Dwight G.
Abstract : Purpose: To develop a method for acquiring whole‐heart 3D image‐based navigators (iNAVs) with isotropic resolution for tracking and correction of localized motion in coronary magnetic resonance angiography (CMRA). Methods: To monitor motion in all regions of the heart during a free‐breathing scan, a variable‐density cones trajectory was designed to collect a 3D iNAV every heartbeat in 176 ms with 4.4 mm isotropic spatial resolution. The undersampled 3D iNAV data were reconstructed with efficient self‐consistent parallel imaging reconstruction (ESPIRiT). 3D translational and nonrigid motion‐correction methods using 3D iNAVs were compared to previous translational and nonrigid methods using 2D iNAVs. Results: Five subjects were scanned with a 3D cones CMRA sequence, accompanied by both 2D and 3D iNAVs. The quality of the right and left anterior descending coronary arteries was assessed on 2D and 3D iNAV‐based motion‐corrected images using a vessel sharpness metric and qualitative reader scoring. This assessment showed that nonrigid motion correction based on 3D iNAVs produced results that were noninferior to correction based on 2D iNAVs. Conclusion: The ability to acquire isotropic‐resolution 3D iNAVs every heartbeat during a CMRA scan was demonstrated. Such iNAVs enabled direct measurement of localized motion for nonrigid motion correction in free‐breathing whole‐heart CMRA. Magn Reson Med 77:1874–1883, 2017. © 2016 International Society for Magnetic Resonance in Medicine